Different Cortex Activation and Functional Connectivity in Executive Function Between Young and Elder People During Stroop Test: An fNIRS Study - Huang, Wenhao; Li, Xin; Xie, Hui; Qiao, Tong; Zheng, Yadan; Su, Liujie; Tang, Zhi-Ming; Dou, Zulin (Frontiers in Aging Neuroscience, 2022)
OBJECTIVE: To examine the activation and functional connectivity of the prefrontal and temporal lobe in young and elder during the Stroop test using functional Near-Infrared Spectroscopy (fNIRS). METHODS: 33 healthy volunteers (20 young, mean age: 23.7 ± 3.9 years old; 13 elders mean age: 63.9 ± 4.0 years old) participated in the study. All subjects were asked to finish the Stroop Color-Word Test. The oxygenated hemoglobin concentration (Delta [HbO2]) signals and the deoxygenated hemoglobin (Delta [HbR]) signals were recorded from Temporopolar Area (TA), pars triangularis Broca's area (Broca), Dorsolateral prefrontal cortex (DLPFC) and Frontopolar area (FA) by fNIRS. The coherence between left and right Frontotemporal lobe Delta [HbO2] oscillations in four frequency intervals (I, 0.6–2 Hz; II, 0.145–0.6 Hz; III, 0.052–0.145 Hz and IV, 0.021–0.052 Hz) was analyzed using wavelet coherence analysis and wavelet phase coherent. RESULTS: Only elders shows significant activation in DLPFC, Broca, FA and TA during the Stroop test but young did not show significant differences. In the functional connectivity of task states, younger people had stronger connections between differentColor-Wordions in both the left and right brain when compared with the elderly (P<0.05). In particular, the left and right DLPFC showed stronger connection strength in most of the brain areas. The result suggested that younger people had stronger functional connectivity of brain areas than older people when completing the task. Conclusion: According to these results, although the cortical activation in the elder was higher than the young, the young showed stronger connectivity in most of the brain areas than the elder. Both sides of DLPFC and right Broca area were the most significant cortical activation in Stroop test. It was suggested that the decrease of functional connectivity in the elder was resulted in the atrophy of white matter which we should pay more attention to.